Analysis of factors affecting the quality of health service satisfaction in schizophrenic patients at outpatient mental health in Ernaldi Bahar hospital: A cross-sectional study - Titin Elfitriany; Akhmad Dwi Priyatno; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Background: Quality healthcare services in hospital settings must comply with established standards to ensure patient safety and satisfaction. Noncompliance with these standards may lead to dissatisfaction and potential malpractice. However, there is limited research assessing patient satisfaction with the quality of healthcare services among schizophrenic patients at the outpatient mental health unit of Ernaldi Bahar Hospital, South Sumatra Province. Objective: This study aimed to analyze the factors affecting patient satisfaction with the quality of healthcare services among schizophrenia patients at the outpatient mental health clinic of Ernaldi Bahar Hospital. Methods: This quantitative research employed a cross-sectional design. The study population comprised 7,463 patients who visited the outpatient mental health unit of Ernaldi Bahar Hospital between January and March 2025. Using purposive sampling, 100 respondents were selected. Data were collected in May 2025 through a structured questionnaire and analyzed using univariate, bivariate, and multivariate logistic regression tests. Results: The results revealed that several variables were significantly associated with patient satisfaction: education level (p = 0.068; OR = 0.462; 95% CI: 0.200–1.067), tangibles (p = 0.034; OR = 2.428; 95% CI: 1.062–5.552), assurance (p = 0.000; OR = 5.802; 95% CI: 2.076–16.217), and responsiveness (p = 0.098; OR = 2.595; 95% CI: 0.817–8.243). The dominant influencing factors were assurance and responsiveness, indicating that patients valued the reliability and promptness of service. Conclusion: There is a significant relationship between education level, tangibles, assurance, and responsiveness with patient satisfaction among schizophrenic patients receiving outpatient care. Assurance and responsiveness were the most dominant predictors of satisfaction. Enhancing responsiveness—particularly in promptly addressing patient complaints, requests, and emotional needs—alongside maintaining assurance through professional competence and empathy, can improve overall service quality and satisfaction.